Tackling anti-microbial resistance: Ethical framework for rational antibiotic use - Littmann, Jasper; Rid, Annette; Buyx, Alena (European Journal of Public Health, 2018)
Background: To reduce the effect of antimicrobial resistance and to preserve antibiotic effectiveness, clinical guidelines and health policy documents call for the rational use of antibiotics, which aims to reduce unnecessary or minimally effective antibiotic use. Methods: Through ethical analysis, we show that rational use programmes can lead to ethical conflicts, because they sometimes place patients at risk of harm-for example, a delayed switch to second-line antibiotics for community-acquired pneumonia can lead to substantial increases in mortality. Results: Implementing the rational use of antibiotics can lead to conflicts between promoting patients' clinical interests and preserving antibiotic effectiveness for future use. The resulting ethical dilemma for clinicians, patients and policy makers has so far not been adequately addressed. Conclusions: Existing guidance for acceptable risks in clinical research can help to define risk thresholds for the rational use of antibiotics. We develop an ethical framework that allows clinicians and policy-makers to evaluate policies for rational antibiotic use in six practical steps. This framework can help guide clinical practice and health policy.
CRIS-Team Scopus Importer:2023-03-08